2022
DOI: 10.21873/invivo.12847
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Preoperative Albumin-Bilirubin Status in Esophageal Cancer Patients Who Receive Curative Treatment

Abstract: Background/Aim: The albumin-bilirubin (ALBI) score, which evaluates the perioperative liver function, was developed, and had a clinical impact on both the short-and long-term oncological outcomes in some malignancies. We evaluated the clinical impact of preoperative albuminbilirubin status in patients with resectable esophageal cancer who received curative treatment. Patients and Methods: The study included 121 patients who underwent curative surgery followed by adjuvant chemotherapy for esophageal cancer betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…This ability of ALBI to discriminate liver function in patients without cirrhosis could be useful in clinical practice (and should be assessed prospectively) in several scenarios such as the baseline evaluation and later monitoring of liver function in noncirrhotic patients submitted to liver resection, under therapies with potential impact on liver function (for instance, oxaliplatin or irinotecan chemotherapy for cancer patients), with liver metastasis from any cancer, and others. [24][25][26] Moreover, our results also support the possibility that ALBI could be used to estimate noninvasively the degree of fibrosis and differentiate cirrhosis from non-cirrhotic stages, as recently suggested. 23 This study has some limitations.…”
Section: Discussionsupporting
confidence: 87%
“…This ability of ALBI to discriminate liver function in patients without cirrhosis could be useful in clinical practice (and should be assessed prospectively) in several scenarios such as the baseline evaluation and later monitoring of liver function in noncirrhotic patients submitted to liver resection, under therapies with potential impact on liver function (for instance, oxaliplatin or irinotecan chemotherapy for cancer patients), with liver metastasis from any cancer, and others. [24][25][26] Moreover, our results also support the possibility that ALBI could be used to estimate noninvasively the degree of fibrosis and differentiate cirrhosis from non-cirrhotic stages, as recently suggested. 23 This study has some limitations.…”
Section: Discussionsupporting
confidence: 87%
“…However, Feng et al [ 19 ] demonstrated that baseline bilirubin and serum proteins were not associated with the prognosis of advanced pancreatic cancer. Instead, a Japanese study indicated that a low albumin-bilirubin (ALBI) grade is related to better OS and RFS in esophageal cancer patients[ 20 ]. AC will directly affect the biliary tract, and the presence of jaundice can predict malignant ampullary strictures[ 21 ]; thus, their disease may be diagnosed at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who died had a significantly lower ALBI score than those who survived (2.8±0.4 vs 3.4±0.7, p < 0.001). Patients who died had a significantly lower GCS score (median [Q 1 -Q 3 ]; 8 [3][4][5][6][7][8][9][10][11][12][13] vs 15 [14][15], p < 0.001) but higher ISS (median [Q 1 -Q 3 ]; 33 [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] vs 20 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], p < 0.001) than the surviving patients.…”
Section: Comparison Of Patient and Injury Characteristics In Death An...mentioning
confidence: 99%
“…[21][22][23][24][25][26][27] Patients with cholangiocarcinoma, 28 intrahepatic cholangiocarcinoma, 29 pancreatic cancer with liver metastases, 30 colorectal cancer with liver metastases, 31 and primary biliary cholangitis 32 can all benefit from knowing their ALBI grade as a prognostic indicator. Additionally, other non-hepatological disorders, including aortic dissection, 33 heart failure, 34,35 acute pancreatitis, 36 lung cancer, 24,37,38 esophageal cancer, 39 gastric cancer, 40 lung cancer, 41 and medulloblastoma, 42 have shown a high correlation between ALBI and death.…”
Section: Introductionmentioning
confidence: 99%